THE ROLE OF EXTRACURRICULAR ACTIVITIES IN IMPROVING THE EFFECTIVENESS OF TEACHING - Xusanov Axmadjon Jurayevich; Andrew Herman (Galaxy International Interdisciplinary Research Journal, 2023)
One of the main tasks of educational institutions is to develop students’ ability to use their knowledge and skills creatively at the level of love for work and creativity. It is important to engage students in technical creativity in solving this task, because the current stage of science and technology development requires that all sectors of public administration be brought to the advanced marks of science and technology. That is why young people who are embarking on an independent life should have time-consuming, high intellectual and physical perfection, deep knowledge of the scientific, technological and economic foundations of manufacturing, the need to treat work intelligently, creatively, and in order to carry out these tasks effectively, they need to take a new phase of education in schools and a high level of student knowledge development of activity is a pressing problem of modern times.